2012
DOI: 10.1016/j.ijid.2012.05.1031
|View full text |Cite
|
Sign up to set email alerts
|

Traditional risk factors for Helicobacter pylori infection not found among patients undergoing diagnostic upper endoscopy—Republic of Georgia, 2007–2008

Abstract: In this large cohort with gastrointestinal symptoms, only age >30 years and living in the capital were significant factors associated with infection. Lower SES, less education, and crowding did not confer an increased risk, in contrast to the findings of previous studies. Population-based studies are needed to identify potential routes and risk factors of H. pylori infection in ROG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…However, regardless of whether 14 C‐UBT or serological assay was used, participants over 50 years exhibited a gradual decline in the H. pylori infection rate. This result was similar to reports from Linqu and Yangzhong of China [6, 14], but inconsistent with other studies which reported that old age groups were at a higher risk for infection than young ones [26]. There are two possible reasons to explain these findings.…”
Section: Discussioncontrasting
confidence: 64%
“…However, regardless of whether 14 C‐UBT or serological assay was used, participants over 50 years exhibited a gradual decline in the H. pylori infection rate. This result was similar to reports from Linqu and Yangzhong of China [6, 14], but inconsistent with other studies which reported that old age groups were at a higher risk for infection than young ones [26]. There are two possible reasons to explain these findings.…”
Section: Discussioncontrasting
confidence: 64%
“…The virulence factors of H. pylori are important risk determinants but are not sufficient to induce the full development of severe gastroduodenal disease. The host’s genetic and sociocultural factors also contribute to the risk of pre-cancerous lesions and gastric cancer [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown ambiguous associations between H. pylori infection and age. Tarkhashvili et al showed that H. pylori infection was associated with older age, and they attributed the higher infection rate to lower socioeconomic conditions (18). A study that aimed to explore associations between H. pylori infection and metabolic syndrome also showed a higher prevalence in older age groups (19).…”
Section: Discussionmentioning
confidence: 99%